2020
DOI: 10.1111/cpr.12871
|View full text |Cite
|
Sign up to set email alerts
|

Chrysophanic acid shifts the differentiation tendency of BMSCs to prevent alcohol‐induced osteonecrosis of the femoral head

Abstract: Objectives Osteonecrosis of the femoral head (ONFH), largely caused by alcohol abuse, is a refractory bone disease characterized by the impaired capacity of osteogenic differentiation of bone mesenchymal stem cells (BMSCs), as well as the disordered adipocyte accumulation. Chrysophanic acid (CPA) is a natural anthraquinone which has lipid regulation and bone protection capacity. The aim of this study was to reveal the potential function of CPA and the underlying mechanisms for the alcohol‐induced ONFH. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Therefore, BMSCs are the key factor for the development and treatment of alcoholic ONFH. In the present study, ethanol significantly inhibited the proliferation and osteogenic differentiation of BMSCs, which was consistent with our previous research 21,26 . Moreover, Alda‐1 could obviously reverse the inhibition of ethanol‐induced proliferation and osteogenic differentiation of BMSCs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, BMSCs are the key factor for the development and treatment of alcoholic ONFH. In the present study, ethanol significantly inhibited the proliferation and osteogenic differentiation of BMSCs, which was consistent with our previous research 21,26 . Moreover, Alda‐1 could obviously reverse the inhibition of ethanol‐induced proliferation and osteogenic differentiation of BMSCs.…”
Section: Discussionsupporting
confidence: 92%
“…Our results also demonstrated that ethanol significantly promoted the adipogenic differentiation, fortunately, Alda‐1 significantly retarded alcohol‐induced adipogenesis of BMSCs via AMPK pathway. Our previous studies indicated that ethanol promoted adipogenesis leading to ONFH by AMPK pathway 21 . Moreover, Alda‐1 activation of ALDH 2 protected against ethanol‐induced cardiac defect and apoptosis via AMPK signalling 30 .…”
Section: Discussionmentioning
confidence: 96%
“…In recent years, traditional Chinese medicines (TCMs) show obvious therapeutic effects and advantages in many disease treatments [ 5 , 6 ]. For instance, andrographolide alleviates oxidative stress and inflammation in arthritis [ 7 ], flavonoids promote bone repair in COM [ 8 ], and betulinic acid relieves synovial inflammation in arthritis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that alcohol can destroy bone homeostasis by directly inhibiting the proliferation and differentiation of bone marrow mesenchymal stem cells (BMSCs). 3 In particularly, alcohol significantly inhibited the proliferation and DNA synthesis of osteoprogenitor cells. 4 Therefore, alcohol is a factor that cannot be ignored to cause osteonecrosis of the femoral head.…”
Section: Introductionmentioning
confidence: 95%
“…9 RAB40C, also known as RARL/RASL8C, is located in 16p13. 3. It is a member of the RAS oncogene family and encodes the protein RAB40C.…”
Section: Introductionmentioning
confidence: 99%